What's Not Converging? East Asia's Relative Performance in Income, Health, and Education - Kenny, Charles (2012)
This paper discusses East Asia's performance in terms of per capita gross domestic product growth rates over the past 40 years and compares that performance to progress primarily on measures of health. It also compares the region to the rest of the world on a set of broader development measures. It looks at the evidence of East Asian regional and global convergence in health and education, alongside evidence from the region matching global evidence of a comparatively weak link between income growth and health and education growth. This finding is echoed by available within-country evidence from the region. This paper discusses what might be behind these results, suggesting the importance of a few simple supply-side interventions coupled with the spread of demand for health and education services as sufficient to drive quality-of-life convergence.